Inventario de insectos asociados con arvenses en plantaciones de Tectona grandis L. f. (teca), con control químico, mecánico y sin control, en los sectores San Carlos del Cantón Quevedo y el Vergel del Cantón Valencia, Provincia de Los Ríos, año 2019. - Mantuano Gonzales, Mishell Stephany (2019)
The present investigation was carried out in two sites of San Carlos del cantón Quevedo, and El Vergel of the Valencia canton, province of Los Ríos, in 2019. The objective of the investigation was to determine the diversity of insects that are associated with weeds in the plantations of Tectona grandis Lf. (teak) with chemical, mechanical control and without control in the sectors already mentioned. The traps were installed in the center of the sampling units, one for each, that is, a total of three traps per site. The samples were collected in a container containing 70% alcohol and 30% distilled water, the identification was carried out following the dichotomous keys. A total of 40 species were collected with a total of 1,128 individuals, with El Vergel 2011 being the site with the greatest diversity with a value of 0.8913 according to Simpson and a value of 2.7 according to Shannon. The site with the lowest diversity was San Carlos 2007 with an average diversity of 0.7554 according to Simpson and a low diversity according to Shannon 1.906. Treatment with the greatest diversity was treatment 1 with 0.8693 (Simpson) and 2.606 (Shannon). The site with the greatest abundance was El Vergel with 337 individuals and the one with the lowest abundance was San Carlos 2010 with 179 individuals. In the treatments: the treatment if control (Treatment 1) was the one that greater number of individuals had with 622 and the one of smaller abundance was the treatment 3 with 162 individuals. Keywords: Inventory, insects, diversity and traps